Fatty degeneration of the heart - Odriozola, Ernesto (1921)
The pathogenic significance of chronic coronary lesions, at the time unknown Laennec and Cruveihier light starts Quain (1850). - Skepticism Stokes to This - Most contemporary authors agree otherwise and develop the view Quain, but confused interstitial fatty infiltration and fatty degeneration of the muscle fibers.